2018
DOI: 10.1016/j.physletb.2018.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Black branes and black strings in the astrophysical and cosmological context

Abstract: We consider Kaluza-Klein models where internal spaces are compact flat or curved Einstein spaces. This background is perturbed by a compact gravitating body with the dust-like equation of state (EoS) in the external/our space and an arbitrary EoS parameter Ω in the internal space. Without imposing any restrictions on the form of the perturbed metric and the distribution of the perturbed energy densities, we perform the general analysis of the Einstein and conservation equations in the weak-field limit. All con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…The gravitating mass perturbs also the background metrics (1). Since the gravitating source is spherically symmetric and pressure in each factor space is isotropic, the perturbed metrics preserves its block-diagonal form (for mathematical justification of this claim, see [12]):…”
Section: Background and Perturbed Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The gravitating mass perturbs also the background metrics (1). Since the gravitating source is spherically symmetric and pressure in each factor space is isotropic, the perturbed metrics preserves its block-diagonal form (for mathematical justification of this claim, see [12]):…”
Section: Background and Perturbed Modelsmentioning
confidence: 99%
“…First, we consider the diagonal components of the Einstein equation (12). To get the expressions for the components of the Ricci tensor, we can use the results of Appendix A in [8].…”
Section: Background and Perturbed Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The only nonzero components of the EMT are, then,T 0 0 ≈ρc 2 andT i k ≈ −δ i k Ωρc 2 for i, k = 4, 5. Such type of perturbation preserves the blockdiagonal form of the perturbed metric [31,35]:…”
Section: Basic Equationsmentioning
confidence: 99%
“…To make the background curved, one needs to introduce a background perfect fluid. The linear multidimensional models with spherical compactification of the internal space were considered in [31][32][33][34][35]. It was shown that the background matter responsible for the internal space curvature has the vacuum-like EoS parameterω 0 = −1 in the external space and some positive EoS parameterω 1 > 0 in the internal space.…”
Section: Introductionmentioning
confidence: 99%